Schistosome serine protease inhibitors: parasite defense or homeostasis? - Quezada,Landys A. Lopez (2011)
Serpins are a structurally conserved family of macromolecular inhibitors found in numerous biological systems. The completion and annotation of the genomes of Schistosoma mansoni and Schistosoma japonicum has enabled the identification by phylogenetic analysis of two major serpin clades. S. mansoni shows a greater multiplicity of serpin genes, perhaps reflecting adaptation to infection of a human host. Putative targets of schistosome serpins can be predicted from the sequence of the reactive center loop (RCL). Schistosome serpins may play important roles in both post-translational regulation of schistosome-derived proteases, as well as parasite defense mechanisms against the action of host proteases.